The HUMAN ONTOLOGY FROM THE PERSPECTIVE OF SEYYED HUSEEN NASR ITS RELEVANCE WITH THE FORMATION OF NATIONAL LEADERSHIP MORALITY: ITS RELEVANCE WITH THE FORMATION OF NATIONAL LEADERSHIP MORALITY - yudha, Gesit; Hermanto, Agus; Hermawan, Andi (Jurnal Studi Islam dan Sosial, 2023)
Ontology explains the nature of everything that exists. In the study of ontology, understanding human nature involves not only comprehending it in actual human terms but, in terms of essence, humans are seen as beings of Monodualism, consisting of two elements yet forming a unity within. Nasr, with his traditional approach, attempts to elucidate the essence of human beings by critiquing the ideologies of the modern world that currently encompass human life. This research is conducted through a literature review, utilizing a descriptive-analytical approach. Sayyed Huseen Nasr consistently ties his discussions to the texts of the Quran and Hadith. Nasr asserts that the essence of human beings cannot be separated from the intervention of God. Thus, the contribution of Nasr's thoughts regarding the concept of human nature in its relevance to morality is that humans are actually related to divine nature and provide direction to the morality of the nation's leadership. In this way, it is possible to create a state of law, not a state of power, in the implementation of state administration.